Estudo do comportamento estrutural de prédios de concreto armado contraventados por núcleo rígido tendo em vista o esforço de torção originado pela ação do vento - Küster, Viviane Kelle Jacundino Porto (Universidade Federal de São Carlos, 2014)
A widely used solution in multiple pavement's edifications to absorb lateral action of the wind and promote structure stability, is to create an element of large rigidity, usually at stairs and elevators areas, denominated central core or bracing core. This structural element is formed by the junction of pillars walls and normally has a C format, what implies having the shear center is not coincidente with the gravity center of the section. It is assumed that always when the resulting of the action does not cross the section s shear center, will occur a tortion of the central core and the building. In order to verify this hipothesis inicially four models were proposed. The first with the shear center coinciding to the ground plan center. The second with the nucleus positioned in a region generally sugested in architectural projects, in other words, aligned to the central porticos, in this case with the CG very close to the center of the ground plan. The third example consists in turning the nucleus totally eccentric. At the fourth example the eccentric nucleus has its rigidity increased. Four aspects are analysed: 1) The structure must be capable of resisting the efforts introduced by the action of the wind; 2) The structure must be rigid enough to satisfy the limits of deformation for the actions in Estado Limite de Serviço; 3) The reinforcement ratio must not exceed to the limits specified in standard; 4) The verifications concerning global stability must be attended. The study shows that the position of the nucleus at the ground plan and slenderness directly influences in the occurence or not of tortion of the building as a whole. Although the wind falls on the nucleus core shear center, being asymmetrical the rigidity of the building in plan, a tortion will occur. May also be concluded that the core bracing does not support the effort proveniente of wind action by itself, before, the other pillars also contribute.
Keywords: Edificações; Torção; Núcleo de contraventamento; Ação do vento; Estabilidade global; Deslocamentos em pilares; Tortion; Bracing core; Action of the wind; Global stability; Displacements; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL